2021
DOI: 10.1163/23641177-bja10031
|View full text |Cite
|
Sign up to set email alerts
|

Virtual and Open Integration of Culture for Education (VOICE) with Science Teacher Candidates from Korea during COVID-19

Abstract: Cultural competencies and confidence in teaching diverse students are needed to close achievement gaps between mainstream and minority students in science. In this study, an online teacher education program, Virtual and Open Integration of Culture for Education (VOICE), was designed to help retain teacher candidates’ science affinities and cultural competency during the COVID-19 pandemic. Thirty-two Korean teacher candidates were selected as culturally responsive instructors who were able to reduce their cultu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 24 publications
0
0
0
Order By: Relevance
“…The author pointed out that designers should be responsive to local specificities such as government regulations and availability of digital resources that may challenge reciprocity in student participation in online classrooms. Yoon's (2021) study demonstrated that contextualizing cultural differences may need to precede online instruction. For example, Korean teachers were better able to teach in an online science classroom, in the Virtual and Open Integration of Culture for Education (VOICE) program, once they understood how American elementary students interpreted science concepts in ways that were culturally different from how the concepts were understood in Korea.…”
Section: Support For Instructors Working With Students From Communitiesmentioning
confidence: 95%
See 2 more Smart Citations
“…The author pointed out that designers should be responsive to local specificities such as government regulations and availability of digital resources that may challenge reciprocity in student participation in online classrooms. Yoon's (2021) study demonstrated that contextualizing cultural differences may need to precede online instruction. For example, Korean teachers were better able to teach in an online science classroom, in the Virtual and Open Integration of Culture for Education (VOICE) program, once they understood how American elementary students interpreted science concepts in ways that were culturally different from how the concepts were understood in Korea.…”
Section: Support For Instructors Working With Students From Communitiesmentioning
confidence: 95%
“…Responsiveness can be seen also through how frameworks guide teacher training by bridging understanding across borders or by creating spaces for new understandings. Yoon et al (2021) used Cultural Intelligence (CQ) (Earley & Ang, 2003) as a measurement of cultural awareness outcomes (cognitive, motivational, and behavioral) by Korean science teachers' online encounters with US minority students. Gleason and Jaramillo Chavez's (2020) research used Hansen's (2017) lens of Cosmopolitanism in studying teacher candidates' collaboration and intercultural communication.…”
Section: Findings Question 1: What Are Theories and Conceptual Models...mentioning
confidence: 99%
See 1 more Smart Citation
“…CRT is the answer to what is a good strategy for teaching diverse classes. Cultural engagement in education increases students' cultural mastery and interest in science (Yoon et al, 2021). Culture is not only seen as the identity of each student but can be utilized as a potential learning resource, and students feel real context.…”
Section: Culturally Responsive Teaching (Crt)mentioning
confidence: 99%
“…No. 1 April 2023, ISSN: 2620 technology, especially in conveying difficult subject matter like mathematics and science (Celi, 2021;Yoon et al, 2021).…”
Section: Table 3 Description Of Thementioning
confidence: 99%